2016
DOI: 10.1016/j.rmed.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of mechanical ventilation in patients with idiopathic pulmonary fibrosis in the United States: A nationwide retrospective cohort analysis

Abstract: In a large national cohort, the in-hospital mortality of patients with IPF who are mechanically ventilated is approximately 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 22 publications
(14 reference statements)
4
62
2
5
Order By: Relevance
“…More recently, two national cohorts were reported. Analysis of the US cohort revealed an in-hospital mortality of approximately 50% (51.6% with IMV and 30.9% in NIV) among 2481 patients with IPF who were mechanically ventilated [50]. Analysis of the Japanese cohort demonstrated that among 209 patients receiving an average of 12.8 days of IMV, short-term (within 30 days) survival was 44.6% and long-term (within 90 days) survival of 24.6%.…”
Section: Improving Prognosismentioning
confidence: 99%
“…More recently, two national cohorts were reported. Analysis of the US cohort revealed an in-hospital mortality of approximately 50% (51.6% with IMV and 30.9% in NIV) among 2481 patients with IPF who were mechanically ventilated [50]. Analysis of the Japanese cohort demonstrated that among 209 patients receiving an average of 12.8 days of IMV, short-term (within 30 days) survival was 44.6% and long-term (within 90 days) survival of 24.6%.…”
Section: Improving Prognosismentioning
confidence: 99%
“…It may be that more contemporary management approaches to respiratory failure and acute lung injury (e.g. low tidal volume ventilation) are improving in-hospital survival (61); this is an area in need of careful study.…”
Section: Managementmentioning
confidence: 99%
“…Invasive mechanical ventilation has been consistently associated with a very high mortality among IPF patients in the ICU setting (>90%) [87] . However, in a recent, large, nationwide cohort analysis in the USA, in-hospital mortality among patients with IPF requiring invasive mechanical ventilation was approximately 50% [88] . This trend may also be due to contemporary management approaches to acute lung injury (lung-protective ventilation strategies).…”
Section: Mechanical Ventilationmentioning
confidence: 99%